Rice straw co-digestion potential with cow dung and poultry droppings for maximizing biogas production in Bangladesh - Chayan Kumer Saha; Jannatoon Nime; Mst. Lucky Khatun; Tafura Hoque Sharna; Md. Monjurul Alam (Heliyon)
Rice is the staple food of the people of Bangladesh. Burning and landfilling of carbon-rich rice straw (RS) causes greenhouse gas emissions. On the other hand, cow dung (CD) and poultry droppings (PD) produced from the livestock sector in Bangladesh could be a potential threat to the environment if the wastes are not properly managed. However, anaerobic co-digestion of RS with CD and PD could be an effective means of biogas generation. Therefore, co-digestion of CD and PD with carbon-rich RS was conducted in batch assay at seven different mixing ratios (100:0, 90:10, 70:30, 50:50, 30:70, 10:90, 0:100) separately. Mesophilic condition (35 °C) was maintained for 92 days of digestion time to investigate biogas production potential and find out optimal mixing ratios of both co-digestion sets. Co-digestion of CD and RS at 70:30 ratio significantly showed maximum biogas yield (441.7 ± 54.1 ml/gVS). Additionally, an increase in biogas yield in this ratio was 212.11 % and 38.10 % compared to mono-digestion of CD and RS, respectively. Another co-digestion set of PD with RS showed highest biogas yield (344.8 ± 22.3 ml/gVS) at 90:10 ratio. The 90:10 ratio of PD and RS improved biogas yield by 173.16 % and 7.8 % as compared to mono-digestion of PD and RS, respectively. Co-digestion of RS with CD and PD had a statistically significant effect (P ≤ 0.05) on biogas production. Furthermore, kinetic modelling outcomes suggested the modified Gompertz model as ideal for forecasting biomethane production over time in both cases. The findings of this study will help in the implementation of ACoD at the field level.